HOW EARLY DO ANTIBIOTICS HAVE TO BE TO IMPACT MORTALITY IN SEVERE SEPSIS? A PROSPECTIVE, OBSERVATIONAL STUDY FROM AN EMERGENCY DEPARTMENT - Siddiqui, Shahla; Salahuddin, Nawal; Raza, Adeel; Razzak, Junaid (Journal of Ayub Medical College Abbottabad, 2009)
Background: The objective of this study was to assess the promptness of antibiotic administration to patients presenting with sepsis and the effects on survival and length of hospitalization. Methods: Consecutive, adult patients presenting with Systemic Inflammatory Response Syndrome (SIRS) to the emergency department of the Aga Khan University hospital were enrolled in a prospective, observational study over a period of 4 months. Univariate, multivariate regression modeling and oneway ANOVA were used to examine the effects of various variables on survival and for significant differences between timing of antibiotic administration and survival, two-sided p values <0.05 were considered significant. Results: One hundred and eleven patients were enrolled. Severe sepsis was present in 52% patients; the most frequent organism isolated was Salmonella typhi (18%). Overall mortality was 35.1%. One hundred (90.1%) patients received intravenous antibiotics in the Emergency room; average time from triage to actual administration was 2.48±1.86 hours. The timing of antibiotic administration was significantly associated with survival (F statistic 2.17, p=0.003). Using a Cox Regression model, we were able to demonstrate that survival dropped acutely with every hourly delay in antibiotic administration. On multivariate analysis, use of vasopressors (adjusted OR 23.89, 95% CI 2.16,263, p=0.01) and Escherichia coli sepsis (adjusted OR 6.22, 95% CI 1.21,32, p=0.03) were adversely related with mortality. Conclusions: We demonstrated that in the population presenting to our emergency room, each hourly delay in antibiotic administration was associated with an increase in mortality. Keywords: sepsis, shock, antibiotics, emergency department